Optimization method of testing web-resources based on multicriterial approach - Кулишова, Нонна Евгеньевна; Глуходед, Марина Игоревна (Eastern-European Journal of Enterprise Technologies, 2012)
The number of types of software has been increased. When creating a typical web project (website, portal) about half of the time and more than 50% of the total cost is testing the developed program or system. Testing is an important step in creating a software product. The purpose of this paper is to develop such an algorithm of optimal use of testing methods to reduce the time on testing period, but with preservation of the maximum test coverage, and, consequently, the quality of a web resource. The task of making optimal decisions is to choose among the many possible solutions. The method, which integrates set of steps and actions to be taken to get the best result - an optimal set of test methods for web-resource, is developed. Input data for the method is a set of well-known testing techniques. As part of the solution of the problem a set of characteristics is formed and evaluated by the group of experts in the field. In this paper, a method for the optimal set of accounting methods for effective testing of web resources based on a survey of experts in the field, is proposed. To solve this problem we must solve some specific issues: - finding the optimal set of test methods for specific cases of the website based on a survey of experts in the field of testing and applying multi-criteria optimization; - developing an algorithm of test methods to ensure the highest quality web resource